2013
DOI: 10.1002/bies.201200125
|View full text |Cite
|
Sign up to set email alerts
|

Quality control of mitochondria during aging: Is there a good and a bad side of mitochondrial dynamics?

Abstract: Maintenance of functional mitochondria is essential in order to prevent degenerative processes leading to disease and aging. Mitochondrial dynamics plays a crucial role in ensuring mitochondrial quality but may also generate and spread molecular damage through a population of mitochondria. Computational simulations suggest that this dynamics is advantageous when mitochondria are not or only marginally damaged. In contrast, at a higher degree of damage, mitochondrial dynamics may be disadvantageous. Deceleratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…The importance of this flexibility has been recently suggested from mathematical modeling in which mitochondrial dynamics, mitochondrial biogenesis, mitophagy, and mitochondrial damage were analyzed. This study revealed that the deceleration of fission and fusion appears to be beneficial for an organism when mitochondrial damage passed specific threshold levels 36 38 . The elucidation of the underlying mechanisms controlling such flexibility including the sensing of impairments and imbalances and the induction of potential compensatory mechanisms certainly holds the key for understanding the complex network of pathways involved in lifespan control, aging and the development of mitochondrial diseases.…”
Section: Discussionmentioning
confidence: 85%
“…The importance of this flexibility has been recently suggested from mathematical modeling in which mitochondrial dynamics, mitochondrial biogenesis, mitophagy, and mitochondrial damage were analyzed. This study revealed that the deceleration of fission and fusion appears to be beneficial for an organism when mitochondrial damage passed specific threshold levels 36 38 . The elucidation of the underlying mechanisms controlling such flexibility including the sensing of impairments and imbalances and the induction of potential compensatory mechanisms certainly holds the key for understanding the complex network of pathways involved in lifespan control, aging and the development of mitochondrial diseases.…”
Section: Discussionmentioning
confidence: 85%
“…In summary, CS-induced mitochondrial hyperfusion might serve as an adaptive response to increase mitochondrial ATP production to cope with CSE-induced cell damage. A hyperfused mitochondrial network, however, may render the cell more vulnerable to additional stress, as it attenuates mitochondrial quality control (14). Moreover, because elongated mitochondria are spared from removal by autophagy (16), sustained mitochondrial hyperfusion, attributable to continuous and chronic exposure to stress, might further increase susceptibility upon additional stress of the mitochondrial network.…”
Section: Discussionmentioning
confidence: 99%
“…In this mathematical model, the generation of molecular damage, spread of damage, biogenesis of cellular components, mitochondrial fission and fusion, and mitophagy, as a type of selective autophagy, are modeled and simulated. The results indicate that the analyzed pathways effectively cooperate in a regulated way to keep mitochondria functional over time 29 , 30 . While the role of mitochondrial dynamics on aging was first reported in P. anserina 31 and the impact of the generation of damage has been previously demonstrated, 32 the impact of autophagy on aging has not been investigated yet although autophagy has been studied in the context of vegetative incompatibility between strains of different genotypes and found to protect cells against death 33 - 35 …”
Section: Introductionmentioning
confidence: 96%